Epicardial Ablation for Arrhythmogenic Disorders in Patients with Brugada Syndrome - Andrea Matteucci; Marco Valerio Mariani; Luca Sgarra; Michela Bonanni; Marco Frazzetto; Vincenzo Mirco La Fazia; Nicola Pierucci; Carlo Lavalle; Claudio Pandozi; Federico Nardi; Furio Colivicchi (Biomedicines)
Brugada syndrome (BrS) is an inherited arrhythmogenic disorder characterized by distinct electrocardiographic patterns and an increased risk of sudden cardiac death due to ventricular arrhythmias. Effective management of BrS is essential, particularly for high-risk patients with recurrent arrhythmias. While implantable cardioverter–defibrillator (ICD) is effective in terminating life-threatening arrhythmias, it does not prevent arrhythmia onset and can lead to complications such as inappropriate shocks. Epicardial ablation has emerged as a promising treatment option for patients with recurrent ventricular arrhythmias and frequent ICD interventions. This review examines the latest advancements in the management of Brugada syndrome, focusing on the role and rationale of epicardial ablation for the treatment of patients at risk of sudden cardiac death.